Mandates of maternity at a science museum, from should to must - David Haldane Lee (Qualitative Research in Medicine & Healthcare)
A pregnancy exhibit at a science museum is an opportunity to research how medical advice is communicated and interpreted. This paper is about the Beginning of Life area of an exhibition called The Amazing You at the Tampa Museum of Science and Industry, where exhibits are prescriptive as well as descriptive. Expectant women are urged to deliver full-term, normal birthweight babies, by behaving according to prescribed medical norms. This study provides ethnographic descriptions of the exhibits, as well as insights from museum visitors who were interviewed. The exhibits, which emphasize fetal rights and maternal duties, are interpreted and critiqued by women visitors. As the exhibits climb towards greater realism (from euphemistic computer graphics to actual fetal specimens) visitors encounter assertions of fact that precede sometimes tacit directives to undergo a medicalized pregnancy. Exhibits are viewed from the perspective of speech act theory, presenting a new approach to health communication research. I argue that this science center exhibit tells people what to do, in addition to passing on information.